HUBUNGAN PERCEIVED ORGANIZATIONAL STRUCTURE TERHADAP EMPLOYEE ENGAGEMENT YANG DIMODERASI OLEH PERCEIVED ORGANIZATIONAL SUPPORT - Andarini, Diah (Arthavidya Jurnal Ilmiah Ekonomi, 2020)
Abstract: This study aims to examine the relationship between perceived organizational structure and employee engagement which is moderated by perceived organizational support. Organizational support provides assistance for employees in adapting to existing organizational structures. A good organizational structure will improve employee performance and create employee attachments to the work environment. Data from this study were taken from 90 employees of PT. PLN (Persero) Surabaya Office with proportional sampling method. The data analysis technique in this study used multiple linear regression. The results of this study indicate that perceived organizational structure has a positive and significant effect on employee engagement, and perceived organizational support reinforces the positive influence of perceived organizational structure on employee engagement. Keywords: perceived organizational structure, employee engagement, perceived organizational support